2022
DOI: 10.3390/pharmaceutics14102150
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Scaffolds Containing Extracts of Stryphnodendron adstringens and Abarema cochliacarpa for Wound Healing: In Vivo Proofs of Concept

Abstract: The present work aimed to evaluate the healing effect of hydrophilic polymeric resorbable biomembrane scaffolds containing plant extracts obtained from two different species, both popularly known as Stryphnodendron adstringens or Barbatimão. The hydrogel-based scaffolds were characterized and submitted to biological tests using Wistar rats to evaluate their healing capacity. The wound retraction index and the evaluation of the inflammatory process and tissue collagenization were recorded. The extracts showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 65 publications
0
2
0
1
Order By: Relevance
“…Scientific reports corroborate the strong wound-healing activity of S. adstringens [7][8][9][10][11] and experimental findings suggest its therapeutic effect on some chronic inflammatory or infectious conditions [12][13][14][15][16][17][18]. These results suggested that S. adstringens had a relevant anti-inflammatory role, involving its ability to modulate bone marrow macrophage polarization showing a reduction in interleukin 6 (IL-6) cytokines.…”
Section: Introductionmentioning
confidence: 67%
“…Scientific reports corroborate the strong wound-healing activity of S. adstringens [7][8][9][10][11] and experimental findings suggest its therapeutic effect on some chronic inflammatory or infectious conditions [12][13][14][15][16][17][18]. These results suggested that S. adstringens had a relevant anti-inflammatory role, involving its ability to modulate bone marrow macrophage polarization showing a reduction in interleukin 6 (IL-6) cytokines.…”
Section: Introductionmentioning
confidence: 67%
“…No documento intitulado "Hydrophilic Scaffolds Containing Extracts of Stryphnodendron adstringens and Abarema cochliacarpa for Wound Healing: In Vivo Proofs of Concept", descreve o potencial cicatrizante de uma biomembrana de S. adestringens, foram confirmados o potencial dessa espécie em processo cicatricial em um período de três -sete dias, se tornando um organismo vegetal promissor no processo de reparação tecidual (ALVES, et al 2022).…”
Section: Resultsunclassified
“…This is because thin and delicate type III collagen fibrils are initially deposited in order to provide a three-dimensional scaffold that guides endothelial migration during the early stages of granulation tissue development. Subsequently, these fibers are progressively replaced by thicker type I collagen fibers with greater tensile strength as the scar tissue matures [ 73 ].…”
Section: Discussionmentioning
confidence: 99%